Gaya Kepemimpinan Perempuan dalam Proses Kemajuan Pembangunan di Desa (Jurnal Strategi dan Bisnis, 2023)
Regional autonomy is the rights, authorities and obligations of the regions to regulate and manage themselves by the local government. So the existence of a leader in government organizations is needed, especially village government. Women's leadership, which is often discussed by all groups, in fact, not a few government institutions are led by a female leader and experience an increase in the achievements and performance of an institution. The results of research that has been conducted by researchers, that the leadership style of the female village head in village development in Karangjati Village uses a leadership style with a situational approach. In addition, the village head makes decisions in a relatively democratic style, communication refers to a consultative style, supervision refers to a partnership style and motivating refers to a participatory style. So the style of the leader is not only based on gender, in fact the village leader of Karangjati is a woman and she is also able to lead the village and bring many changes to the people and village of Karangjati